Minat Beli Ulang dari Segi Pengalaman dan Persepsi Nilai Produk Aqua (Studi Konsumen di Kota Bandung) - Anita Silvianita; Zidney Izzatul Ichsan (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
This study was conducted to determine whether the experience and perception of value positively and significantly influence the interest of consumers to repurchase Aqua Products in the city of Bandung. This study has three variables: experience and perception of importance as the independent variable and interest in repurchase as the dependent variable. All data in this study were obtained by distributing questionnaires to consumers using Aqua products in Bandung with a sample of 384 people. The research method is a descriptive causal method through purposive sampling data collection techniques. The Data were processed using multiple linear regression analysis. The results of this study are the discovery of the significance of the results for the influence of X1 and X2 together to Y is equal to 0.000 < 0.05 and the value of F count 48.344 > F table 2.63, so it can be concluded that the independent variables consisting of experience, and perception of value together have a significant influence on consumer interest in aqua products, which means that the greater the creation of knowledge and perception of the importance of Aqua Products, the higher the consumer interest in repurchasing Aqua Products.